Endometriosis misdiagnosed as a metastatic ovarian tumour (2019)
Endometriosis is a debilitating problem with pain in the short term and high risk of infertility later. It is an oestrogen-dependent condition found in about 10% of women of reproductive age, about 1/3 of infertile women and as high as 80% of women with chronic pelvic pain. The condition is not well understood and thus associated with misdiagnosis and delayed diagnosis. Higher rates of misdiagnosis occur in blacks and this is especially for pelvic tumors-fibroids and ovarian tumors. We present here the case of a 30-year-old nullipara, who had an umbilical nodule (Sister Mary Joseph’s) and was found on imaging to have a pelvic tumor which was suspected to be an ovarian cancer. Diagnostic laparoscopy during the menstrual phase however revealed endometriosis in early stage. Misdiagnosis of endometriosis has potential to distort the course of the disease and endanger fertility prospects; early laparoscopic evaluation of patients with unclear pelvic pathologies would help to prevent this occurrence.